Contraband guides : race, transatlantic culture, and the arts in the Civil War era - Kaplan, Paul H. D. (Paul Henry Daniel), 1952- (The Pennsylvania State University Press, 2020)
"Explores the theme of race in nineteenth-century transatlantic culture, focusing on how American concepts of race were intertwined with the ongoing cultural exchanges that Americans had with European artistic traditions"--